Mainstreaming the adaptations and reducing the vulnerability of the poor due to climate change - Ranganathan, C.R.; Kuppannan, Palanisami; Kakumanu, Krishna Reddy; Baulraj, A. (Asian Development Bank, 2010)
Many rural poor people in developing countries depend on agriculture and are highly influenced by climatic change. Hence, sustainable livelihood approaches are used at both policy and project level to initiate new poverty reduction activities and modify existing activities to improve livelihood incomes. Practices relevant to climate change adaptation around the world are wideranging and include development of technology, management, infrastructure, livestock, groundwater, and knowledge. Both structural interventions (such as building flood embankments, dikes, or seawalls or enhancing the natural setting or landscape) and nonstructural interventions (policies, knowledge development, awareness, methods and operating practices, including participatory mechanisms) have helped to reduce the impact of climate change. Further, market-based instruments such as credits and crop insurance were also developed to help poor households in many developing countries to cope with the uncertainties. The uptake of such adaptation practices is lagging, however, but informal institutions are playing a key role as they rely on enforcement methods and are not supported by the government. Mainstreaming adaptation and enhancing adaptive capacity could be increased by encouraging partnerships between informal processes and formal interventions to facilitate adaptation by the poor. The cost of adaptation is also significantly higher in developing countries. Nonetheless, more attention is needed in addressing future climate scenarios through agricultural research and development, irrigation development, infrastructure, and improved irrigation efficiency.